Lessons from the climate anxiety counseling booth : how to live with care and purpose in an endangered world - Schapira, Kate (Hachette Go, an imprint of Hachette Books, 2024)
"In 2013, Kate Schapira sat in her office at Brown University and read about acidic waters, ecological imbalance, dead zones, and zombie ecosystems. Before then, she'd had the same broad understanding of climate change that most people did at the time, but these articles on the permanent disappearance of coral reefs filled her with such hopelessness that she desperately needed an outlet-someone or someone to talk to who understood how she was feeling. Soon, she was setting up a Peanuts-style "The Doctor Is In" booth in her hometown of Providence, Rhode Island, to talk about climate change with her community. Ten years and over 1,200 conversations later, Schapira channels all she's learned into an accessible, understandable, and aware guide for processing climate anxiety and affecting real change in people's lives and communities. Filled with stories, questions, and exercises, "Lessons from the Climate Anxiety Counseling Booth" focuses on five action verbs that readers can use to build their climate resilience: recognize, release, find, build, and become. All the stories, questions, and practices included in this book have helped someone find what they wanted or needed, whether in the moment or for the years to come. Through their use of this book, readers will move through their personal and general climate anxiety, frustration, helplessness, and grief toward a sense of shared purpose and community care. "Lessons from the Climate Anxiety Counseling Booth" meets readers where they are with thoughtful and practical strategies to help solve this growing crisis in a way that doesn't sugarcoat the realities or scream fragility and instead offers communal support"--